Chasing Water / Elegy of an Olympian - Akashic Books; Ervin Anthony; Markides Constantine (2016)
A provocative and refreshingly honest redemption memoir. Preface, The Dive, The Ready Room, All in the Game, Gold, The Iron Fence, A Nervous Condition, Experiments, Over the Water, The Heat, Wet above Black Bough, Turbulence, In a Dark Pool, Brother Saint, Lethe's Edge, Serpent Skin, Into the Flood, The Crystalis, The Resurfacing, Meditations, The Year of the Water Dragon, Still Water, Epilogue, Appendixes.